2006
DOI: 10.1158/1535-7163.mct-05-0199
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepinedione inhibitors of the Hdm2:p53 complex suppress human tumor cell proliferation in vitro and sensitize tumors to doxorubicin in vivo

Abstract: The activity and stability of the p53 tumor suppressor are regulated by the human homologue of the mouse double minute 2 (Hdm2) oncoprotein. It has been hypothesized that small molecules disrupting the Hdm2:p53 complex would allow for the activation of p53 and result in growth suppression. We have identified small-molecule inhibitors of the Hdm2:p53 interaction using our proprietary ThermoFluor microcalorimetry technology. Medicinal chemistry and structure-based drug design led to the development of an optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(91 citation statements)
references
References 59 publications
1
85
0
4
Order By: Relevance
“…6A). Other potent MDM2 antagonists with similar binding modes and desired in vivo activities include spiro-oxindole (Ding et al 2006;Shangary et al 2008a;Shangary et al 2008b) and benzodiazepinedione analogs (Grasberger et al 2005;Koblish et al 2006) (Fig. 6B).…”
Section: Targeting the P53 Pathway: Mdm2 Mdmx Sirtuins And Beyondmentioning
confidence: 99%
“…6A). Other potent MDM2 antagonists with similar binding modes and desired in vivo activities include spiro-oxindole (Ding et al 2006;Shangary et al 2008a;Shangary et al 2008b) and benzodiazepinedione analogs (Grasberger et al 2005;Koblish et al 2006) (Fig. 6B).…”
Section: Targeting the P53 Pathway: Mdm2 Mdmx Sirtuins And Beyondmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19] In cells with functional p53, the p53 activity is primarily inhibited through direct and tonic interaction with the MDM2 protein. [20][21][22] Treatment of various tumor cells with inhibitors of the MDM2-p53 interaction results in rising p53 levels and subsequent induction of cell-cycle arrest and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Several compounds have been identified that prevent the association between p53 and Mdm2 (Nutlin3 and Rita; refs. [7][8][9]. In addition, compounds that target the ubiquitin ligase domain of Mdm2 can also protect or engage p53 activity (10).…”
Section: Introductionmentioning
confidence: 99%